(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Hemolytic Disease of the Fetus and Newborn (HDFN) is the leading cause of anemia in fetuses and neonates, primarily due to maternal red blood cell alloantibodies that cross the placenta and attack fetal RBC with paternal antigens. The prevalence of these alloantibodies among pregnant women varies by country. This study aims to assess the local prevalence of clinically significant alloantibodies in pregnant women. Methods This retrospective study was conducted on total 6135 pretransfusion testing of pregnant women obtained from the hospital Laboratory Information System between 2020 and 2021 at the Blood Bank Unit of Hospital Canselor Tuanku Muhriz, University Kebangsaan Malaysia. Patients’ age, parity, transfusion history, sensitizing events and antibody screening results were collected. A descriptive analysis was conducted on the prevalence, frequency, specificity of clinically significant antibodies, and associated risk factors. Association of age and clinically significant alloantibodies were assessed using the chi-square test (p < 0.05). Results The prevalence of clinically significant alloantibodies was 0.8%. Anti-Mia was the most common alloantibody, followed by anti-E and anti-M. No significant association was detected between maternal age and clinically significant alloantibodies. Six primigravida patients had clinically significant alloantibodies—anti-M, anti-Mia, and anti-E—without any sensitizing events, suggesting they may be naturally occurring. All pregnant women should ideally receive red cell antibody screening during routine antenatal check-ups to address the risk of HDFN. However, in resource-limited settings with low prevalence of significant alloantibodies and HDFN, this may not be cost-effective. Targeted screening for high-risk populations could be a better alternative. BJMS, Vol. 24 No. 04 October’25 Page : 1138-1145